APPLICATION GUIDANCE TO READ QUR’AN WITH TAHSIN METHOD USING MICROSOFT VISUAL BASIC VERSION 6.0 - Hendarismanto Hendarismanto; Ire Puspa W., SKom., MMS Ire Puspa W., SKom., MMS (Jurnal Sistem Informasi, 2006)
At this writing the guidance discussed about the application reading the Qur'an Tahsin method by using Microsoft Visual Basic version 6.0. This application is made with the aim of making the Koranic learning more Variatif. Tahsin language by language means to improve. The definition of Tahsin is a method to correct common errors in reading the Qur'an. Basically, reading the Qur'an easy to know when the punctuation and expenditure places a letter in the Qur'an. Hopefully with the existence of this paradigm Tahsin method among the public about the difficulty of learning the Qur'an can be changed.